2022
DOI: 10.1002/pc.27201
|View full text |Cite
|
Sign up to set email alerts
|

Vibration behavior of a carbon fiber‐reinforced polymer composite sandwich panel: Rhombus core versus elliptical core

Abstract: Exploring lightweight sandwich structures with excellent load-bearing and vibration damping performances is one of the important topics in structural and functional applications. The aim of the present research is to design, fabricate carbon fiber-reinforced polymer (CFRP) sandwich panels with rhombus cores and investigate their modal characteristics by comparing with the traditional elliptical sandwich structure experimentally and numerically. In order to obtain modal properties including natural frequencies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In papers [23,24,25,26], the results of calculations and modeling of the behavior of sandwich plates of different shapes and made of different materials using the theory of shear deformation are presented. The results of experimental studies of three-layer plates are also presented [27].…”
Section: Literature Analysismentioning
confidence: 99%
“…In papers [23,24,25,26], the results of calculations and modeling of the behavior of sandwich plates of different shapes and made of different materials using the theory of shear deformation are presented. The results of experimental studies of three-layer plates are also presented [27].…”
Section: Literature Analysismentioning
confidence: 99%
“…For example, Gholizadeh Eratbeni et al 7 obtained the natural frequencies and mode shapes of a glass fiber composite sandwich panel through experimental and numerical modal analysis. In another article, Gholizadeh Eratbeni and Rostamiyan 8 compared the vibrational behavior of two carbon fiber composite sandwich panels, one with a lattice core and the other with an elliptical core, using modal analysis and finite element methods. Gholizadeh Eratbeni and Rostamiyan 9 calculated and analyzed the vibrational characteristics of a carbon fiber and glass fiber composite sandwich panel using finite element and experimental modal analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Kermani and Ehsani 20 analyzed the multi‐objective optimization on the composite sandwich structures in order to maximize the natural frequencies by minimizing the weight and cost of the structures. Eratbeni and Rostamiyan 21 experimentally studied the modal characteristics of the sandwich structure with rhombus core using roving hammer technique and compared with an elliptical core. Under free‐free boundary conditions, the experimental results demonstrated that the natural frequencies of the rhombus core sandwich structures are significantly greater than those of the elliptical core sandwich structures.…”
Section: Introductionmentioning
confidence: 99%